2004
DOI: 10.1111/j.0022-202x.2004.23460.x
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of VEGF165 Concomitantly Expressed with its Receptors Promotes Growth and Survival of Melanoma Cells through MAPK and PI3K Signaling

Abstract: Vascular endothelial growth factor (VEGF) is an important mediator of tumor-associated angiogenesis, and consequently it has been associated with metastasis. We report here that the overexpression of VEGF(165) in melanoma xenografts promotes an acceleration of tumor growth and an increase in angiogenesis as well as the spontaneous metastasis formation. In addition, VEGF receptors (VEGFR)1, VEGFR2 and neurophilin-1 are expressed in A375 melanoma cells. Forced overexpression of VEGF in these cells induces cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 46 publications
10
85
0
Order By: Relevance
“…3, both isoforms stimulated the proliferation of breast tumor cells. However, VEGF 165 appeared to be more potent as previously reported for endothelial cells (Graells et al 2004). Quantitatively, both cell lines responded similarly to increasing concentrations of VEGF 165 and VEGF 121, though with 200 ng/ml, VEGF 165 BT-474 cells responded significantly better than T47-D cells (as also observed in Fig.…”
Section: Influence Of Vegf Isoforms On Proliferation Of Tumor Cellssupporting
confidence: 84%
See 1 more Smart Citation
“…3, both isoforms stimulated the proliferation of breast tumor cells. However, VEGF 165 appeared to be more potent as previously reported for endothelial cells (Graells et al 2004). Quantitatively, both cell lines responded similarly to increasing concentrations of VEGF 165 and VEGF 121, though with 200 ng/ml, VEGF 165 BT-474 cells responded significantly better than T47-D cells (as also observed in Fig.…”
Section: Influence Of Vegf Isoforms On Proliferation Of Tumor Cellssupporting
confidence: 84%
“…2D, VEGF-dependent proliferation of breast cancer cells was dependent on VEGFR2. Other investigators have shown that the interaction of VEGF with VEGFR2 can activate the PI3-kinase/Akt-dependent signaling pathway and the mitogen activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signal transduction pathway (Graells et al 2004, Svensson et al 2005. We used specific inhibitors of four different signaling modules to identify the pathway involved in mediating VEGFinduced tumor cell proliferation in BT-474 and T47-D breast cancer cells.…”
Section: Vegf-induced Cellular Proliferation Involves the Mapk Pathwaymentioning
confidence: 99%
“…Similarly, a great majority of human cancers overexpress or contain constitutively activated receptor and non-receptor tyrosine kinases and/or growth factor autocrine loops that also result in hyperactivation of the Raf-1/Mek-1/Erk1/2. (Di Marco et al, 1989;Fleming et al, 1992;Watanabe et al, 1996;Graells et al, 2004). More importantly, hyperactivation of this pathway is critical to the growth and survival of human tumors (Sebolt-Leopold et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In many cancers, both the overexpression of the growth factor and the receptor, besides mutations at the cytoplasmic tyrosine kinase domain, contribute to constitutive signaling; thus, these receptors make attractive targets for targeted therapies [80]. For example, in the transition from radial to vertical growth phase, melanoma as well as angiogenesis is heralded by both the expression and release of vascular endothelial growth factor (VEGF), which facilitates both growth of new blood and the tumor [29,81,82] …”
mentioning
confidence: 99%